PENGAWASAN JAM OPERIONAL TEMPAT VIDEO GAME/PLAYSTATION DI KECAMATAN SAIL KOTA PEKANBARU - Mohd. Reza Syaputra; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In an affort to curb the place of entertainment, the government of Pekanbaru City make local regulation Number 03 of 2002 about general entertaintment, one of which is Video Game/Playstation. This regulation aims to curb the Video Game/Playstation so that in the implementation of this business operations do not make a disadvantage, a danger, and disturbance to the society especially surrounding environment. Based on the experience of research in field, most place of Video Game/Playstation do not comply with local regulation that made by government of Pekanbaru City. The purpose of this study is to know how the surveillance of Video Game/Playstation by Civil Service Police Unit of Pekanbaru and to know the obstacle factors that affect surveillance Video Game/Playstation in Pekanbaru City.This study conducted in Sail District Pekanbaru City with using qualitative descriptive method, data was collected through observation and interviews. This research done by using theory of Manullang, which set the stanrdards, make an assesment and take the corrective action.The result of this study conclution, supervision by Civil Service Police Unit of Pekanbaru still not implemented effectively, this proven by the fact that most of Video Game/Playstation in Sail District still not comply the rules that made by government of Pekanbaru City. This happened because of the supervision proccess do not make maximum effort in implementation to rules, Socialization and the sanction.Keyword: Supervision, Operational Hours, Playstation